2022
DOI: 10.1136/jnis-2022-019527
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin versus aggressive antiplatelet therapy for acute carotid stenting plus thrombectomy in tandem occlusions: ETIS Registry results

Abstract: BackgroundPatients treated with acute carotid stenting (CAS) may have higher odds of a favorable outcome than those treated without CAS during thrombectomy in tandem occlusions. Antiplatelet therapy is associated with CAS to avoid stent thrombosis, which occurs in around 20% of patients and negatively impacts outcomes. In this study we compared two antiplatelet strategies in tandem occlusion strokes treated with CAS and intracranial thrombectomy in clinical practice.MethodsThe Endovascular Treatment in Ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Focusing exclusively on patients undergoing eCAS for tandem lesion stroke, a recent single center analysis in a cohort of 132 patients28 observed increased rates of intracranial recanalization, significantly reduced stent thrombosis, and improved clinical outcomes in case of aggressive periprocedural antiplatelet treatment without heparin, compared with aspirin monotherapy. A similar analysis of 187 patients from the ETIS Registry29 compared aspirin versus more intensive antiplatelet therapies (with additional heparin in 11% of cases) and observed improved carotid stent patency without safety concerns. The results of the present study are in keeping with these previous findings and provide additional evidence in favor of more intensive periprocedural antiplatelet treatment in this setting.…”
Section: Discussionmentioning
confidence: 93%
“…Focusing exclusively on patients undergoing eCAS for tandem lesion stroke, a recent single center analysis in a cohort of 132 patients28 observed increased rates of intracranial recanalization, significantly reduced stent thrombosis, and improved clinical outcomes in case of aggressive periprocedural antiplatelet treatment without heparin, compared with aspirin monotherapy. A similar analysis of 187 patients from the ETIS Registry29 compared aspirin versus more intensive antiplatelet therapies (with additional heparin in 11% of cases) and observed improved carotid stent patency without safety concerns. The results of the present study are in keeping with these previous findings and provide additional evidence in favor of more intensive periprocedural antiplatelet treatment in this setting.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, 71 observational studies were potentially eligible for inclusion, and 34 reached qualitative synthesis (figure 1 for PRISMA flow-chart, online supplemental table 2 for study details). Among them, two observational studies compared noAPT versus SAPT,18 19 three compared noAPT versus DAPT,18 20 21 two compared noAPT versus GPI,18 19 five compared SAPT versus DAPT,18 22–25 four compared SAPT versus GPI18 19 26 27 and four compared DAPT versus GPI,18 28–30 while the remainder focused on a single APT regimen 31–50…”
Section: Resultsmentioning
confidence: 99%
“…Periprocedural antithrombotic therapy in the context of eCAS aims to ensure durable patency of the stent, which is tied to good clinical outcome 52 53. Hemodynamic and embolic mechanisms associated with carotid artery re-occlusion can cause ischemic core growth or ischemia in new territories, increasing the risk of bleeding and poor recovery 27. Early adjuvant antithrombotic therapy with eCAS to maintain stent patency may translate into a more effective procedure overall, but at the potential cost of a higher risk of symptomatic intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…When emergent CAS is needed to treat a tandem stenosis during mechanical thrombectomy, the French ETIS (Endovascular Treatment in Ischemic Stroke) Registry investigators have concluded that an aggressive antiplatelet approach—intraprocedural loading with oral or intravenous glycoprotein IIb/IIIa inhibitors or P2Y12 inhibitors followed by a maintenance intravenous infusion or oral dosing (depending on the agent)—was superior to aspirin alone to prevent subacute stent thrombosis, and was not associated with higher rates of intracranial hemorrhage 85. Post-procedurally an intravenous regimen was typically converted to an oral regimen, often within 24 hours after the procedure.…”
Section: Disease-specific Considerationsmentioning
confidence: 99%